The contribution of small-scale fisheries to the community food security of one South African coastal community - Macdonald, Margaret (Department of Environmental and Geographical Science, 2020)
Small-scale fisheries contribute to the food security of a significant portion of the global population through direct consumption and indirectly as a vital source of income. Approximately, 50 million individuals involved in capture fisheries are small-scale fishers and they contribute to 80 percent of the global catch that is used for domestic consumption. Smallscale fishers provide their immediate communities with a vital source of protein. The sector enables an income source through full-time or part-time work to vulnerable coastal communities. In South Africa, approximately 28,000 small-scale fishers rely on marine resources for food security and livelihoods; however, continued marginalisation of small-scale fishers through discriminatory fisheries regulations favouring the large-scale fisheries sector and poor reallocation of access rights challenges the contribution of small-scale fisheries for community food security. While there is evidence that suggests small-scale fisheries in South Africa contribute to the food security of coastal communities, there is little know about the extent of the contribution as well as how the sector contributes to community food security and what factors influence community food security outcomes. The purpose of this research was to examine the contribution of small-scale fisheries to the community food security of one South African coastal community. Lambert’s Bay, Western Cape served as the case study and a mixed methods approach was employed to address three research objectives. Forty household surveys were completed at fisher and non-fisher households to examine the current level of household food security within the community and address the first research objective. Secondly, focus group discussions were completed with men and women to understand perceptions of food security and the food culture of the community. Lastly, the third objective was to examine the potential impacts of a reconfigured market on the local food system. This objective was addressed through a scenario planning workshop that was conducted with fishermen and women. This research utilised a community food security lens to broadly examine the role of smallscale fisheries to food security. Community food security is a holistic term that builds upon food security, food sovereignty and cultural food security but explores food security at both the household and community level as well as how outcomes are shaped by socio-economic, institutional and environmental drivers. The lens enabled the reframing of food security within the context of a fishing community and provided a scope to address the research objectives. Overall, Lambert’s Bay case study indicates high levels of food insecurity characterised by significant seasonal variation and low dietary diversity. Reported consumption of fish was relatively low; however, during the Snoek run, findings indicated consumption of fish throughout the community increased. Moreover, the Snoek season, is significant for its contribution food security indirectly as it provides livelihoods for many individuals. Historically, fishing activities and fish was a key aspect to the cultural identity of Lambert’s Bay. While fish remains a component of culture, the decline in traditional food ways associated with fish suggested a weakening of its cultural significance. Environmental, economic and institutional factors threaten the contribution of small-scale fisheries to the community food security of Lambert’s Bay. Most notably, poor governance in the small scale-fisheries sector has compromised the role of fish for food, livelihoods and culture. Secondly, environmental changes due to climate change and human activities reduce access and availability of fish for food and livelihoods. The key finding of this research was that small-scale fisheries contributes to the community food security of Lambert’s Bay through direct consumption and indirectly though the provision of livelihoods. Seasonality, unfavourable fishing conditions as well as the presence of Snoek, a migratory species, dictates the role of small-scale fisheries for food security. Poor seasonal fishing conditions negatively impacts the consumption of fish throughout the community as well as income for fishers. Conversely, the Snoek season provides critical livelihoods opportunities for community members and increased consumption of fish throughout the community. Environmental and institutional factors influence food security outcomes derived from small-scale fisheries. In addition, the prevalence of traditional food practices and the functionality of the social economy associated with fish is adversely affected by these drivers. This research contributes to scholarship within the small-scale fisheries and food security sphere as well as food systems research. It highlights the interconnectedness of various factors and the complexity of coastal food systems through the application of a community food security lens. A deeper understanding of the factors that influence food security outcomes in the context of fishing communities is advantageous as it can guide targeted research and initiatives that strengthen the well-being of fisher communities.